Local Angiotensin Pathways in Human Carotid Atheroma: Towards a Systems Biology Approach. (18th May 2015) - Bricca, Giampiero; Legedz, Liliana; Nehme, Ali; Ayari, Hanène; Paultre, Christian; Hodroj, Wassim; Li, Jacques-Yuan; Randon, Jacques; Lohez, Olivier; Dhaouadi, Nedra; Gustin, Marie Paule; Cerutti, Catherine
Abstract : We will summarize the data we have obtained in human carotid artery concerning the organization of an extended local renin angiotensin aldosterone system and its variations at different stages of atheroma. In a system view, we propose a model where concomitant increase in angiotensin and glucocorticoid signaling is induced and amplified in VSMC while vascular smooth muscle cells transdifferentiate toward a lipid storing phenotype.